2009
DOI: 10.1111/j.1365-246x.2009.04217.x
|View full text |Cite
|
Sign up to set email alerts
|

Seismicity in a model governed by competing frictional weakening and healing mechanisms

Abstract: S U M M A R YObservations from laboratory, field and numerical work spanning a wide range of space and time scales suggest a strain dependent progressive evolution of material properties that control the stability of earthquake faults. The associated weakening mechanisms are counterbalanced by a variety of restrengthening mechanisms. The efficiency of the healing processes depends on local material properties and on rheologic, temperature, and hydraulic conditions. We investigate the relative effects of these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 140 publications
(209 reference statements)
1
5
0
Order By: Relevance
“…Finally, our results show that small changes in the friction coefficient can easily explain deviations from the periodic earthquake recurrence model without the need of assuming either a temporally constant failure stress (time‐predictable model) or a coseismic stress drop to a temporally constant level (slip‐predictable model). This finding is consistent with the study by Hillers et al. (2009), who observed in 1D numerical experiments that frictional weakening and healing significantly increase the variability in earthquake frequency and size.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Finally, our results show that small changes in the friction coefficient can easily explain deviations from the periodic earthquake recurrence model without the need of assuming either a temporally constant failure stress (time‐predictable model) or a coseismic stress drop to a temporally constant level (slip‐predictable model). This finding is consistent with the study by Hillers et al. (2009), who observed in 1D numerical experiments that frictional weakening and healing significantly increase the variability in earthquake frequency and size.…”
Section: Discussionsupporting
confidence: 93%
“…, 2007). One‐dimensional numerical models showed that the competition between frictional weakening and healing cause considerable variability in the frequency‐size distribution of earthquakes (Hillers et al. , 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The evolution of fault strength during the seismic cycle exerts an important control on earthquake size and recurrence [Hiller et al, 2009;De Paola et al, 2012;Hampel and Hetzel, 2012;McLaskey et al, 2012]. In order for a fault (or fault patch) to undergo repeated earthquake failure, it must have the ability to restrengthen during the interseismic period [Brace and Byerlee, 1966;Brace, 1972;Dieterich, 1972Dieterich, , 1978.…”
Section: Introductionmentioning
confidence: 99%
“…We uses a cellular automata model composed by cell (the unit of system) and evolution rule after comparing previous research works [10]- [18].…”
Section: Model Designmentioning
confidence: 99%